2016
DOI: 10.1186/s12917-016-0702-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of susceptible hosts in canine distemper virus infection: a systematic review and data synthesis

Abstract: BackgroundCanine distemper virus (CDV) is the etiological agent of one of the most infectious diseases of domestic dogs, also known as a highly prevalent viral infectious disease of carnivores and posing a conservation threat to endangered species around the world. To get a better panorama of CDV infection in different Orders, a retrospective and documental systematic review of the role of CDV in different non-dog hosts was conducted. The bibliographical data were collected from MedLine/PubMed and Scopus datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(154 citation statements)
references
References 72 publications
3
148
0
3
Order By: Relevance
“…A surrogate model based on the study of the Canine distemper virus (CDV)—a closely related morbillivirus that infects a broad range of carnivores including ferrets or dogs—represents an attractive alternative. CDV causes a similar overall pathogenesis in its different hosts, but the disease severity varies from moderate in dogs, to completely lethal in highly susceptible species, such as ferrets and many wild carnivores [4,5]. The clinical signs include fever, often a characteristic rash, diarrhea, nasal discharge, conjunctivitis, and generalized immunosuppression, thereby reproducing the disease spectrum seen in MeV patients (Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…A surrogate model based on the study of the Canine distemper virus (CDV)—a closely related morbillivirus that infects a broad range of carnivores including ferrets or dogs—represents an attractive alternative. CDV causes a similar overall pathogenesis in its different hosts, but the disease severity varies from moderate in dogs, to completely lethal in highly susceptible species, such as ferrets and many wild carnivores [4,5]. The clinical signs include fever, often a characteristic rash, diarrhea, nasal discharge, conjunctivitis, and generalized immunosuppression, thereby reproducing the disease spectrum seen in MeV patients (Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…Since the first isolation of CDV by Carré in 1905, CDV still remains a challenge to veterinarians and pet owners (9). Hemagglutinin protein is the suitable target to study genetic divergence and molecular epidemiology due to high mutation of the H gene (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are not always suitable conjugated antispecies antibodies for wildlife species available for use with IFAT or ELISA. A systematic literature review of all possible non-dog hosts of CDV showed that ELISA was used 13.8 % of the time as serological test, followed by IFAT (7.7 %) [29]. The highly specific and sensitive serum-neutralization test is more commonly used (75.4 %) for the detection of CDV from serum samples and can be seen as the gold standard for detecting antibodies [29,59,115,116].…”
Section: Serological Assaysmentioning
confidence: 99%
“…Sequence analyses indicate that the H-protein undergoes genetic drift related to geographical regions, clustering into America 1 (including almost all commercially available vaccine strains), America 2, Asia 1 and 2, Europe/ South America 1, Europe wildlife, South America 2 and 3, Arctic, Rockborn-like, Africa and Africa 2 [28][29][30]. Genotypes are defined on the basis of strains falling within the same clade sharing >95 % amino acid similarity in their Hprotein [31].…”
Section: Viral Propertiesmentioning
confidence: 99%
See 1 more Smart Citation